Russia – Measures Concerning Traffic in Transit (WTO). (October 2019) - Hartmann, Stephanie
Abstract : On April 5, 2019, a World Trade Organization (WTO) panel (Panel) issued its decision in the dispute Russia – Measures Concerning Traffic in Transit . This decision is notable because it is the first instance in which a WTO panel has been called on to interpret the national security provision of the General Agreement on Tariffs and Trade (GATT 1994), Article XXI.